Dating the Tejo river lower terraces in the Ródão area (Portugal) to assess the role of tectonics and uplift - Cunha, Pedro P. (2008)
The Tejo river is one of the major drainages in Iberian Peninsula; it is a long-lived system (ca. 3.4 Ma) and provides an archive of long-term landscape development and environmental change controlled by tectonics, climate and eustasy. The most upstream Portuguese reach of the Tejo river, ~ 200 km from the Atlantic coast, shows evidence for five fluvial terraces (T1 to T5) with elevations reaching more than 120 m above the modern river bed. A chronological framework for these terraces is established here by integrating geomorphological, stratigraphical and archaeological information with ages from luminescence dating. Optically stimulated luminescence dating of K-feldspar, (involving the correction for anomalous fading of the luminescence signal), indicates that the younger terraces have a probable age range of: T5 -- 31 to 40 ka; and T4 -- 100 to ~ 280 ka. We deduce that the related major fluvial changes are likely to have been as follows: ~ 10 m of aggradation from ~ 280 to 100 ka (0.06 m/ka); 14 m of incision from 100 to 40 ka (0.23 m/ka); 8 m of aggradation from 40 to 31 ka (0.89 m/ka); 16 m of incision during the last 31 ka (0.52 m/ka). These values indicate that the duration and rate of both aggradation and river downcutting episodes were variable. There is widespread evidence for neotectonic activity in this intraplate region. Neither eustatic nor climatic changes during the Quaternary provide clear trends that might explain the observed pattern of valley incision, thus we conclude that this tectonic activity is the most likely driving mechanism. In the study area, the probable age of the Tejo river sediments deposited before the beginning of valley incision allows the calculation of a time-averaged incision rate of ~ 0.07 to 0.10 m/ka over the last ~ 2.6 Ma. This long-term incision was probably determined by an increase in the relative uplift rate, resulting from the intensification of intraplate compressive stress. During the late Cenozoic fluvial incision stage, the Ródão depression underwent less uplift than the adjacent areas along the river, in which the Tejo has incised a narrow valley into basement rock, with almost no terrace development. Terrace formation was also promoted by soft bedrock (Tertiary arkoses) and by impoundment of alluvium behind resistant barriers crossed by the river. Geomorphological evidence for terrace tectonic offset was also supported by luminescence dating.